Survival is Just the Beginning: Quality of Life in Patients (QoL) with Intraoral and Extraoral Squamous Cell Carcinoma (SCC) - Mohamad Rifki Adli Mustawan; Widyanti Soewoto (Rumah Sakit Umum Daerah Dr. Moewardi, 2026)
Introduction Squamous cell carcinoma (SCC) continues to be a health problem worldwide with far reaching effects not only on survival but on patient's quality of life (QoL). Health-related quality of life (HRQoL) assessment sheds lights on overall disease and its treatment impact. Method In this cross-sectional study was performed on 53 patients diagnosed with SCC, which included 36 intraoral and 17 extraoral cases. Sociodemographic data was collected and the QoL was assessed by using the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ-C30) and short form-36 (SF-36). The data were analyzed using Mann-Whitney U test and Spearman’s correlation. Results Among 53 SCC patients (36 intraoral, 17 extraoral; mainly middle-aged females of low socioeconomic status), overall Quality of Life (QoL) score did not differ between groups. In summary, the analyses revealed additional differences in QoL determinants as patients with intraoral head and neck Squamous cell carcinoma (SCC) QoL was driven towards functional domains whereas symptom-related determinants were dominated for extraoral SCC patients. There was no statistically significant difference in overall QoL (p = 0.839) between groups. Discussion This study provides evidence suggesting that QoL impairments associated with intraoral SCC and with extraoral SCC are primarily driven by symptom burden and pain, and that there is no difference between the groups in overall quality of life (QoL). The relationship between QoL and functional limitations was more pronounced for intraoral SCC, whereas symptom severity had a greater impact on mental status for extraoral SCC. These results are consistent with existing evidence that SCC affects multiple dimensions of health irrespective across the sites of the tumor. There are QoL data available for management of various chronic conditions, and they highlight the importance of more comprehensive, patient-centred care that emphasizes early symptom control along with optimal pain management and functional rehabilitation strategies. Conclusion Demographics do not affect the quality of life of SCC patients, as clinical variables like symptoms, pain, and limitations impact it more than demographic data. Patients with intraoral SCC also experienced moderate QoL, highlighting opportunities for better symptom control and psychosocial support to improve overall patient health-related QoL.